Bubble translation at low-frequency actuation in a resonator-shaped microfluidic chamber - Shang, Xiaopeng (2018)
Bubble dynamics in bulk flow has been widely investigated at high-frequency actuation (normally above 20 kHz, up to several MHz); however, bubble translation in microfluidics has seldom been investigated, especially at low frequencies (below 10 kHz). This paper presents a study on bubble translation in a resonator-shaped microfluidic chamber. The experimental results show that under the actuation at 1 kHz, the bubbles are observed to occur near the center of the chamber, grow up in size and then move upstream against the main flow. The bubble translation upstream against the main flow is attributed to the attraction of the image bubbles which exist behind the chamber sidewall.